Adipose tissue location and contribution to postinjury hypercoagulability. Issue 1 (July 2016) - Winfield, Robert D.; Mellnick, Vincent M.; Chamieh, Jad; Nohra, Eden; Tan, Wen-Hui; Ramirez, Ricardo; Raptis, Constantine; Turnbull, Isaiah R.; Bochicchio, Kelly; Reese, Stacey; Spinella, Philip C.; Bochicchio, Grant V.
Abstract : OBJECTIVES: Obesity is associated with a hypercoagulable state at baseline and following injury. The anatomic location of adipose deposition may influence the type of thrombotic event, with visceral adipose tissue (VAT) associated with arterial thrombosis and subcutaneous adipose tissue (SAT) predisposing to venous thrombosis. We sought to determine whether adipose tissue amount and location correlated with measures of coagulation. METHODS: All adult Level I trauma activations at our institution between January 2013 and August 2014 who underwent admission abdominal computed tomography scan and had admission rotational thromboelastometry measurements were included. Patients were excluded for history of anticoagulant use and known coagulopathy/hypercoagulable state. Admission computed tomography was used to obtain cross-sectional VAT and SAT areas at the umbilicus utilizing a novel software system; VAT and SAT measurements were associated with markers of coagulation utilizing Spearman correlation and stepwise linear regression with significance set at p < 0.05. RESULTS: Two hundred forty-two patients met inclusion and exclusion criteria. Sixty-nine percent of patients sustained blunt injury, 79% were male, mean age was 40 years, 25% were obese or morbidly obese, and mean Injury Severity Scale score was 17. Seventeen percent of patients had acute deep venous thrombosis or pulmonary embolism during hospitalization. Neither SAT nor VAT correlated with prothrombin time, international normalized ratio, or partial thromboplastin time. Subcutaneous adipose tissue correlated positively with platelet count. Visceral adipose tissue and SAT correlated negatively with clot formation time and positively with TEM fibrinogen, α angle, maximum clot firmness, and lysis at 30 minutes; stronger correlations and greater significance were seen between SAT and these measures except for lysis at 30 minutes. Stepwise linear regression confirmed significant relationships between SAT and clot formation time, AA, and maximum clot firmness; VAT showed a significant relationship with TEM fibrinogen. CONCLUSIONS: Increased adipose tissue correlates with relative hypercoagulability following trauma. Subcutaneous adipose tissue shows a stronger relationship with functional measures of coagulation, suggesting that SAT may be associated with hemorrhage resistance and hypercoagulability after injury. LEVEL OF EVIDENCE: Prognostic study, level IV.